2015
DOI: 10.1556/038.50.2015.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the Bionomics of the Pink Stem Borer Sesamia inferens Walker (Lepidoptera: Noctuidae): An Upcoming Pest of Wheat in India

Abstract: Wheat cultivation is of great significance in North-western plains of India and the crop was hitherto considered as almost free from serious insect attack. Recently, Pink stem borer (PSB), Sesamia inferens Walker (Lepidoptera: Noctuidae) has emerged as a new pest and is likely to pose serious threat to the successful cultivation of wheat in the North-western plains of India under largely adopted rice-wheat cropping system. Because of the paucity of data on the developmental biology of PSB on wheat crop regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
5
5
0
Order By: Relevance
“…The mean duration of first to sixth instar larvae (Table 1) 0, 3.4, 3.9, 4.6, 5.3, 6.6 and 13.0 days, respectively. The findings of Joshi (2005), Singh and Kular (2015) who observed that the larvae of S. inferens passed through eight instars to become a pupa also support present findings. The variation in present larval instars and their duration in present findings and findings of earlier workers may be due to the difference in host plant or due to meteorological variation at Hemant Sharma et al / J. Appl.…”
Section: Biology Of S Inferens Eggsupporting
confidence: 90%
See 4 more Smart Citations
“…The mean duration of first to sixth instar larvae (Table 1) 0, 3.4, 3.9, 4.6, 5.3, 6.6 and 13.0 days, respectively. The findings of Joshi (2005), Singh and Kular (2015) who observed that the larvae of S. inferens passed through eight instars to become a pupa also support present findings. The variation in present larval instars and their duration in present findings and findings of earlier workers may be due to the difference in host plant or due to meteorological variation at Hemant Sharma et al / J. Appl.…”
Section: Biology Of S Inferens Eggsupporting
confidence: 90%
“…The findings of Lu and Tan (1981), Reddy (2001) and Aggarwal et al (2004) who reported larval period of S. inferens for 21.9 -28.3 days, 26.10 days and 22.9 days to 23.73 days, respectively also give partial support to the present findings of first generation. Findings of Joshi (2005), Nagarjuna et al (2015) and Singh and Kular (2015) who reported larval duration of 53-74 days, 23-39 days, 68.52 days, respectively also give partial support to the present findings of second generation. The variation in findings of present studies and that of earlier workers may be due to the difference in host plants, genotype or due to meteorological variation at the time of experimentation.…”
Section: Biology Of S Inferens Eggsupporting
confidence: 77%
See 3 more Smart Citations